Improvement of overall equipment efficiency with root cause analysis and TPM strategy: a case study - Ahsanul Abedin (International Journal of Research in Industrial Engineering)
Nowadays, industrial businesses are more aware of the value of machine maintenance, and more especially, the adoption of an effective maintenance strategy. Total Productive Maintenance (TPM), which involves everyday chores involving the entire workforce, increases equipment efficiency, prevents breakdowns, and promotes autonomous operator maintenance. TPM is a fantastic technique for maintaining buildings and machines. This article provides research and a review of TPM implementation in an RMG Industry to help enhance Overall Equipment Effectiveness (OEE). Data from the past have been studied, and the findings obtained in terms of motivated employees, improved OEE, and a decrease in the number of rejects/accidents on the production line are fairly positive. The methodology calls for gradually applying lean principles, Autonomous Maintenance (AM), 5S, and planned maintenance. After TPM deployment on the critical machine, improvements in availability, performance, and quality are seen boosting the overall efficacy of the equipment. A comparison of OEE before and after implementation demonstrates the effectiveness of TPM deployment throughout the industry.